Soft Tissue Sarcoma of the Extremities: What Is the Value of Treating at High-volume Centers?. Issue 4 (April 2019) - Lazarides, Alexander L.; Kerr, David L.; Nussbaum, Daniel P.; Kreulen, R. Timothy; Somarelli, Jason A.; Blazer, Dan G.; Brigman, Brian E.; Eward, William C.
Abstract: Background: For many cancer types, survival is improved when patients receive management at treatment centers that encounter high numbers of patients annually. This correlation may be more important with less common malignancies such as sarcoma. Existing evidence, however, is limited and inconclusive as to whether facility volume may be associated with survival in soft tissue sarcoma. Questions/purposes: The purpose of this study was to examine the association between facility volume and overall survival in patients with soft tissue sarcoma of the extremities. In investigating this aim, we sought to (1) examine differences in the treatment characteristics of high- and low-volume facilities; (2) estimate the 5-year survival by facility volume; and (3) examine the association between facility volume and of traveling a further distance to a high-volume center and overall survival when controlling for confounding factors. Methods: The largest sarcoma patient registry to date is contained within the National Cancer Database (NCDB) and captures > 70% of new cancer diagnoses annually. We retrospectively analyzed 25, 406 patients with soft tissue sarcoma of the extremities in the NCDB from 1998 through 2012. Patients were stratified based on per-year facility sarcoma volume and we used univariate comparisons and multivariate proportional hazards analyses to correlate survival measures with facility volume and various other patient-, tumor-, and treatment-related factors. First, we evaluated long-term survival for all variables using the Kaplan-Meier method with statistical comparisons based on the log-rank test. Multiple patient, tumor, and treatment characteristics were compared between the two facility-volume groups and then included them in the multivariate proportional hazards model. Of the 25, 406 patients analyzed, 3310 were treated at high-volume centers (≥ 20 patients annually) and 22, 096 were treated at low-volume centers. Patient demographics were generally not different between both patient cohorts, although patients treated at high-volume centers were more likely to have larger and higher grade tumors (64% versus 56% size ≥ 5 cm, 28% versus 14% undifferentiated grade, p < 0.001). Results: When controlling for patient, tumor, and treatment characteristics in a multivariate proportional hazards analysis, patients treated at high-volume facilities had an overall lower risk of mortality than those treated at low-volume centers (hazard ratio, 0.81 [0.75-0.88], p < 0.001). Patients treated at high-volume centers were also less likely to have positive margins (odds ratio [OR], 0.59 [0.52-0.68], p < 0.001) and in patients who received radiation, those treated at high-volume centers were more likely to have radiation before surgery (40.5% versus 21.7%, p < 0.001); there was no difference in the type of surgery performed (resection versus amputation) (OR, 1.01 [0.84-1.23], p = 0.883). Conclusions: With the largest patient cohort to date, this database review suggests that certain patients with soft tissue sarcoma of the extremities, particularly those with large high-grade tumors, may benefit from treatment at high-volume centers. Further investigation is necessary to help improve the referral of appropriate patients to high-volume sarcoma centers and to increase the treatment capacity of and access to such centers. Level of Evidence: Level III, therapeutic study.